The Effect of Measuring Return on Assets, Return on Equity, and Operating Income Operating Expense on the Stock Price of Private Mini Bank Companies in 2017-2021 - Nainul Amani; Reswanda (Journal of World Conference (JWC), 2022)
The purpose of this study is to determine the profitability ratio of privet mini bank companies in book 2 bank for the 2017-2021 period. This research was conducted on 27 privet mini-bank companies listed on the Indonesian Stock Exchange for the 2017-2021 period. The data used is secondary data in the form of financial statements. The analysis technique uses multiple linear regression with three independent variables, Return on Asset, Return on Equity and Operating Income Operating Expanse, against the dependent variable of the stock price to test the variable influencing the company’s share price. The research results on private mini bank companies show that stock price movements are not affected and are negative and not significant by Return on Equity in private mini bank companies. This study found that private mini bank companies increasing or decreasing the value of Return on Asset and Operating Income Operating Expenses had a significant and significant effect on the share price of private mini bank companies.